Gender Differences and White Blood Cells on Anxiety Symptoms in Type 2 Diabetes Mellitus: A Community-Based Study - Wiwin Priyantari Heriningsih; Ratna Agustin; Fatin Lailatul Badriyah; Djoko Priyono; Nia Desriva; Yafi Sabila Rosyad; Yohanes Andy Rias (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
Gender differences and type 2 diabetes mellitus (T2DM)-associated inflammatory biomarkers are correlated with high levels of anxiety. However, no study has investigated gender differences and high level of white blood cells (WBC) on anxiety among participants with T2DM in Indonesia. We examined the roles of gender and WBCs on anxiety symptoms in T2DM. A cross-sectional study was performed on 294 patients with T2DM recruited from five community clinics with multistage cluster sampling. Depression, anxiety and Stress-21 (DASS-21) a standardized questionnaire was used to measure anxiety and WBCs was determined using an XP-100 automated haematology analyzer. The adjusted coefficients beta (coefficient Beta) and 95% confidence interval (CI) were performed using a multiple linear regression model. Statistical analyses were calculated using SPSS version 25.0, with a p-value of less than 0.05 set as statistically significant. Females exhibited significantly higher levels of anxiety (Beta=0.26, 95% CI=0.07–0.94) than male respondents. Notably, respondents with WBCs of ³7.576 had significantly higher anxiety (Beta=2.04, 95% CI=1.12–3.71) than patients with WBCs of less than7.576. There was high prevalence of axienty symptoms in this Indonesian sample of respondents. Female and high level of WBCs exist on increasing susceptibility to anxiety symptoms among individuals with T2DM.Abstrak: Perbedaan jenis kelamin dan biomarker inflamasi terkait diabetes mellitus tipe 2 (T2DM) berkorelasi dengan tingkat kecemasan yang tinggi. Namun, belum ada penelitian yang menyelidiki perbedaan jenis kelamin dan sel darah putih (WBC) pada kecemasan di antara penyandang T2DM di Indonesia. Kami memeriksa peran jenis kelamin dan WBCs pada gejala kecemasan untuk penyandang T2DM. Studi cross-sectional dilakukan pada 294 penyandang T2DM yang diperoleh dari lima klinik komunitas dengan multistage cluster sampling. Depresion, Anxiety and Stress-21 (DASS-21) merupakan kusioner standar yang digunakan untuk mengukur kecemasan dan WBCs ditentukan dengan menggunakan penganalisis hematologi otomatis XP-100. Koefisien yang disesuaikan beta (koefisien ?) dan interval kepercayaan 95% (CI) dilakukan dengan menggunakan model regresi linier berganda. Analisis statistik dihitung menggunakan SPSS versi 25.0, dengan nilai p kurang dari 0.05 ditetapkan sebagai signifikan secara statistik. Wanita menunjukkan tingkat kecemasan yang jauh lebih tinggi (? = 0,26, 95% CI = 0,07-0,94) dibandingkan responden laki-laki. Khususnya, responden dengan nilai WBCs ³7.576 memiliki kecemasan yang lebih tinggi secara signifikan (? = 2.04, CI 95% = 1.12–3.71) dibandingkan responden dengan nilai WBCs kurang dari 7.576. Terdapat prevalensi gejala axienty yang tinggi pada sample dari responden sampel di Indonesia dalam penelitian ini. Wanita dan nilai WBCs yang lebih tinngi memiliki peningkatan kerentanan terhadap gejala kecemasan di antara individu dengan T2DM.